PENGARUH PENGGUNAAN MEDIA MINIATUR TERHADAP HASIL BELAJAR PESERTA DIDIK PADA MATA PELAJARAN IPA KELAS V MIN 3 POLMAN KEC. TAPANGO KAB. POLEWALI MANDAR - Asriani, Asriani; Sulaiman, Umar; Sulaiman, Umar; Rosdiana, Rosdiana (Jurnal Ilmiah Pendidikan Madrasah Ibtidaiyah, 2022)
This study discusses the effect of using miniature media on the learning outcomes of fifth grade students at MIN 3 Polman Kec. Tapango Kab. Polewali Mandar, The purpose of this study was to determine 1) the learning outcomes of students in science subjects for class V MIN 3 Polman Kec. Tapango Kab. Polewali Mandar without the use of miniature media 2) student learning outcomes in science subjects for class V MIN 3 Polman Kec. Tapango Kab. Polewali Mandar with the use of miniature media 3) The effect of using miniature media on student learning outcomes in science subjects for class V MIN 3 Polman Kec. Tapango Kab. Polewali Mandar. This research uses a quantitative research type of pre-experimental design and one-group pretest-posttest research design. The population in this study were all students of class V MIN 3 Polman Kec. Tapango Kab. Polewali Mandar, totaling 18 students. The sampling technique used is the saturated sample technique. The instruments used in this study were learning outcomes tests and documentation. Data analysis techniques used inferesnial statistics and descriptive statistics. Based on data analysis using descriptive statistics, the average value of students before the use of miniature media was 50.28 and the average after using miniature media was 79.44. The results of inferential statistical analysis obtained tcount 29.180 while for ttable value of 1.739 which means that tcount > ttable is 29.180 > 1.739. This shows that HO is rejected and H1 is accepted. When viewed from the significant value H1 is accepted if it is significant < α that is 0.000 <0.05. Thus, it can be concluded that learning with the use of miniature media shows that there is an effect of using miniature media on students’ science learning outcomes.